Dispersion beyond miles: configuration and performance in virtual teams. Issue 3 (13th June 2017) - Prasad, Ambika; DeRosa, Darleen; Beyerlein, Michael
Abstract : Purpose: The purpose of this paper is to understand different aspects of structural dispersion in virtual teams (VTs). The study measures five types of dispersion, their impact on VT performance and the moderating effect of electronic communication. Design/methodology/approach: The authors collected data from 44 globally distributed VTs representing 403 members. The authors used details of the members' locations to measure five elements of dispersion for each team: spatial, time-zone, number of locations, extent of numerical balance across locations and extent of isolated members for a team. The authors used two items to assess effective electronic communication and measured team performance on four items from three sources – members, leaders and third-party stakeholders. Findings: Using regression, the authors found that the number of sites, degree of team balance and isolation had a negative impact on team performance. Spatial and temporal dispersion did not impact performance. Effective electronic communication moderated the relationship of team performance with team balance and the number of sites. Research limitations/implications: Study presents novel findings on the role of team configuration in VTs. Limitations: the study provides pointers to the likelihood of a non-linear relationship between spatial distance and performance; however, the scope of the paper does not permit an examination of this model. Future research can study this relationship. Second, the study does not examine how team configuration impacts the team processes that discount performance. Finally, the study treats each index of dispersion as independent of the others. The analysis does not study the interplay between and among the indices. Practical implications: The findings provide clear indicators for managers and researchers of VTs on the issues associated with the location and configuration of the teams. Managers, while designing and managing dispersed members are now informed of the impact of the number of sites and the sub-group dynamics. The study underscores the importance of effective electronic communication in managing dispersion. Social implications: The study presents how faultiness based on location of VT sub-groups (as represented in the configuration of a team) can hamper performance. Literature suggests that this faultiness can also extend to social identities (based on gender, culture, etc.). The indicators provided by this study in this respect provide a topical focus for research because diverse dispersed teams are becoming more prevalent. Originality/value: The study is the first empirical exploration of dispersion in VTs beyond the traditionally acknowledged dimensions of spatial distance and time-zones. It is a timely response to the recent trends in literature. Additionally, the study derives data from a unique data set of global VTs, thus making findings easily generalizable.